On the steady posture of conical spindle distribution used in ball piston pump. (April 2020) - Zhou, Junjie; Jing, Chongbo; Liu, Jianhao
Conical spindle distribution is a new type of hydraulic pump distribution, its steady working conditions refer to a stable position of the shaft and lubrication state under constant operating condition, which directly influences the hydraulic pump efficient and reliable work. In this paper, the Reynolds equation of the tapered flow field is used to establish the lubrication model. The static pressure boundary condition of the distribution pair is obtained by the hydraulic resistance network method. The finite difference method is employed to solve the model. The static and dynamic lubricating performances including the shaft eccentricity and the distribution gap height are obtained by solving the model with a numerical method. Accordingly, the influences of structural parameters and operating parameters on the steady state are investigated, and an experimental test rig is built to validate the model. The experimental results show that the model can predict the higher working pressure which leads to higher distribution gap and eccentricity; the higher the rotational speed is, the smaller the distribution gap and the eccentricity will become, which provides theoretical support for further guidance of the distribution design.